(untitled) (Studia Prawnicze / The Legal Studies, 2001)
Mimo że deklaracja interpretacyjna nie towarzyszyła polskiemu dokumentowi ratyfikacyjnemu odnoszącemu się do Konkordatu, wymiana dokumentów ratyfikacyjnych między Rzecząpospolitą Polską a Stolicą Apostolską praktycznie dotyczyła Konkordatu wraz z wcześniej uzgodnioną i złożoną deklaracją. Od dnia 25 kwietnia 1998 r. (tj. od dnia wejścia w życie) Konkordat obowiązuje w stosunkach między Rzecząpospolitą Polską i Stolicą Apostolską z uwzględnieniem polskiej deklaracji interpretacyjnej. Deklaracja ta stanowi kontekst dla celów interpretacji Konkordatu - w rozumieniu art. 31 Konwencji Wiedeńskiej o prawie traktatów z 1969 r. Prowadzi to do wykładni autentycznej Konkordatu. Odnośne przepisy Konstytucji RP stosują się do Konkordatu rozumianego zgodnie z polską deklaracją interpretacyjną. Although the interpretative declaration did not accompany the Polish instrument of ratification relating to the Concordat, the exchange of instruments of ratification between the Republic of Poland and the Holy See practically concerned the Concordat together with the previously agreed and made declaration. Since 25 April 1998 (i.e. the date of entry into force), the Concordat has been in force in relations between the Republic of Poland and the Holy See, taking into account the Polish interpretative declaration. The declaration provides the context for the interpretation of the Concordat - within the meaning of Article 31 of the 1969 Vienna Convention on the Law of Treaties. This leads to an authentic interpretation of the Concordat. The relevant provisions of the Polish Constitution apply to the Concordat understood in accordance with the Polish interpretative declaration.